The Impact of the Internal Audit in Reducing Credit Risk in Commercial Banks in Kosovo - Siqani, Shqipdona Hashani; Sekiraca, Edona (European Scientific Journal, ESJ, 2016)
Credit risk represents the vast majority of the risk in the context of estimating the capacity of the transfer of risk from commercial banks. Any commercial bank operating, in Kosovo, must have a system for managing credit risk. An important and essential process, such as the management of the credit risk, cannot be carried out without the aid of internal audit. From the survey results, it was concluded that the process of auditing the banks recommended the implementation of policies for managing credit risk of the respective commercial bank’s policy. This also include the policy of credit risk management of the Central Bank of the Republic of Kosovo, implementation of procedures, regulations and rules for credit exposure, loan portfolio diversification, training of staff of the credit risk involved in completing the loan files, etc.